2008
DOI: 10.1128/jcm.01441-07
|View full text |Cite
|
Sign up to set email alerts
|

Lymphadenopathy Caused by Mycobacterium colombiense

Abstract: We report the case of a 3-year-old girl with lymphadenopathy caused by the recently described species Mycobacterium colombiense. M. colombiense is a nonpigmented slow grower that is included in the Mycobacterium avium complex. Partial sequencing of the 16S rRNA gene was used for species identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…We did not have additional clinical data to confirm the clinical significance; however, these data suggest the possibility of disseminated infection due to M. chimaera. We did not identify M. colombiense, a newly described MAC species isolated from the blood and sputum specimens of HIV-infected patients in Colombia (Murcia et al, 2006) and in one case of lymphadenopathy in a 3-year-old Spanish girl (Esparcia et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We did not have additional clinical data to confirm the clinical significance; however, these data suggest the possibility of disseminated infection due to M. chimaera. We did not identify M. colombiense, a newly described MAC species isolated from the blood and sputum specimens of HIV-infected patients in Colombia (Murcia et al, 2006) and in one case of lymphadenopathy in a 3-year-old Spanish girl (Esparcia et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although M. chimaera has been assumed to be highly virulent (7), a recent study in Germany found only 3.3% of 90 M. chimaera isolates to be clinically relevant (10). M. colombiense was fi rst described as a causative agent of mostly disseminated disease in HIV patients from Colombia (11) and was recently isolated from a child with lymphadenopathy in Spain (12). Its isolation in other countries and from respiratory samples in HIV-negative patients has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium colombiense is a MAC species that was isolated from the sputum and blood of HIV/AIDS Colombian patients (28); this strain produced lymphadenopathy in immunocompetent children from France and Spain (29,30) and was associated with pulmonary infections that complicated cases of cystic fibrosis (31). Therefore, this group of opportunistic pathogens have virulence mechanisms that allow them to adapt, survive, replicate, and produce disease in the host.…”
mentioning
confidence: 99%